Evoking death and life in the poetry of lamentation and flight, and observatories in the poetry of pre-Islamic Alsaealik - الفارس, بهاء الدين طارش داود (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
An individual may go through an experience that represents a somewhat adventurous journey, but one to live his entire life as an adventure is not an easy matter. What about a group that lives this life? Al-Sa‘alik poets in pre-Islamic times were known for their strength, courage, and daring. Much of their poetry narrated their adventures, where death was always present before them. The poet from Al-Sa‘alik, who was adventurer in his life and didn’t care about it, was targeted, pursued by the surrounding society, and was forced to live like a wolf in the wilderness, where he would be killed if he did not kill. Perhaps this is what justified their disregard for death or to be afraid of it, to the point that it became a characteristic in their poems.The ultimate goal for the poet was to prove his existence, a goal that made his miserable life easier to bear. It can be said that the obsession with death was reflected in the poetry of this group, and their view to death varied from being dismissive to being fearful of it. It is worth noting that both sides resorted to means of survival, clinging to life. Among these means and methods were fleeing and climbing the mountaintops, which they used to monitor their enemies and avoid risks